Evaluation of Shear Bond Strength and Adhesive Remnant Index of New-Generation Adhesive-Coated Bracket Systems In Comparison With Traditional Systems - Gökay Üstdal; Ayça Üstdal Güney; Eyüp Burak Küçük (Atatürk University, 2024)
Objective: To evaluate the shear bond strength (SBS) and the adhesive remnant index (ARI) of different traditional orthodontic adhesive systems and newly developed pre-coated adhesive systems.Methods: A total of 50 human maxillary premolars were bonded with Clarity advanced ceramic brackets using APC™ Flash-Free, APC™ PLUS, Transbond™ XT Light Cure, Opal® Bond™MV and, Blugloo™ adhesives. All samples underwent thermo-cycling. The SBS was determined using a testometric machine. A stereomicroscope was used to evaluate the adhesive remnant on debonded enamel surface. Differences among the adhesives were tested for statistical significance.Results: Blugloo™ group had the highest SBS (22.69 ± 9.14 MPa). However, there was no significant difference in mean SBS among the groups (p